Особливості математичної культури майбутнього інженера індустрії програмної продукції - Дубініна, Оксана Миколаївна (Донецький національний університет, 2013)
Досліджено особливості математичної культури майбутніх спеціалістів інженерії програмного забезпечення, систематизовано основні компоненти вищеназваної культури, сформульовано визначення поняття математичної культури студентів, які отримують професійну освіту за напрямом підготовки "програмна інженерія", виходячи з основних видів професійної діяльності майбутніх інженерів з виробництва програмного продукту.

Article researches particularities of the mathematical culture of the software industry intended engineers, basic components of the upper called culture are systematized, the definition of the student's who receive professional education in the field of "software engineering" mathematical culture is defined. Note that mathematical culture of specialist in the software industry is a holistic education, with a nucleus, made up of deep fundamental mathematical knowledge and skills, which is based on the cultures of information, algorithmic, logical, graphics, computational, mathematical thinking and mathematical language, and provides a stable, professional competence, professional self-education and self-improvement. A significant number of teachers and scientists recently, namely in the period of exponential growth of the flow of information, support the fact that the formation of mathematical culture in the higher school should be professionally oriented. But the definition and components of many authors differ, as well as different approaches to the study of this phenomenon, criteria and methods of formation of students. And this situation seems logical and consistent if you look at it under a corner of training of students of different specialties. Therefore, in our opinion, this question makes sense to go the way of greater difference. I. e. explore the formation of the mathematical culture of the future experts in software engineering in the process of professional preparation. The specifics of mathematical culture engineer in the software industry but the deep refinement of mathematical knowledge, also includes a high degree of integration in all spheres of human life: whether it's managing space objects or medical experiments, etc. Among the cultures that fill the mathematical culture of the future specialist in software of electronic computing devices provide a special place to algorithmic and information, based on the main types of professional activity. The peculiarities of forming of the mathematical culture of the future engineers, software refer the application of information and computer technologies and specific technologies in the field of software engineering in the process of studying of mathematical disciplines.
Mathematical culture particularities of the software industry intended engineer
Keywords: вища математика; компоненти культури; програмна інженерія; професійна підготовка; culture components; higher mathematics; mathematical culture; software engineering; professional training